METODE DAN MATERI DAKWAH UNTUK WANITA BERMASALAH - Umul Baroroh (Jurnal Ilmu Dakwah, 2018)
Today, along with the pace of information growth, technology raises increasingly complex social problems. The complexity of the problems faced by humans increases and cones like a mountain. For those who are able to overcome social problems will not create new problems. Conversely, for people who are not able to adapt to the development of the times will have new problems. In today's modern era many women have problems that make it one of the "victims" of the progress of the age. This short article elaborates on the methods and material of Dakwah in dealing with problems for women involved in life issues. Analysis of this article states that returning to Dakwah methods and material adapted to al quran and hadith is a panacea that can solve their problems****. Dewasa ini, seiring dengan laju pertumbuhan informasi, teknologi memunculkan persoalan sosial yang semakin komplek. Kompleksitas persoalan yang dihadapi manusia bertambah dan mengerucut seperti gunung. Bagi mereka yang mampu mengatasi masalah sosial tidak akan memunculkan persoalan baru. Sebaliknya, bagi masyarakat yang tidak mampu adaptasi dengan perkembangan zaman akan mempunyai persoalan baru. Di era modern sekarang ini wanita banyak mempunyai persoalan yang menjadikannya sebagai salah satu “korban” atas kemajuan zaman. Artikel singkat ini mengelaborasikan tentang metode dan materi dakwah dalam menghadapi persoalan bagi wanita yang terlibat dalam persolan kehidupan. Analisa artikel ini menyatakan bahwa kembali kepada metode dan materi dakwah yang disesuaikan dengan al qur’an dan hadits merupakan obat mujarab yang dapat menyelesaikan persoalan mereka.